(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this article we will indicate differences and significant questions for present political theory, such as mental violence and political fantasies; resistance; isegoria as a fundamental democratic notion; relations between knowledge, life and science; theoretical space travel; colonial encounters; or relations of alterity and political identity; all from the suggestions encoded in Ray Bradbury´s work, The Martian Chronicles. This is an attempt of theoretical enrichment for political philosophy from a literary text that takes us away from Earth.